SUKSESI SEKUNDER PASCA TEBANG PILIH HUTAN PAMAH DIPTEROCARPS DIDESA TAILELEU, TAMAN NASIONAL PULAU SIBERUT, SUMATERA BARAT - Herwint Simbolon (BERITA BIOLOGI, 2001)
A study on the tree diversity and secondary succession after selective logging of lowland mixed dipterocarps forest has been conducted at three sites (Mongakngai, Kaloat, and Taipah) of Taileleu Village, Siberut Island National Park, West Sumatra. Plot size at each Mongakngai, Kaloat and Taipah site was: 100 x 30m; 100 x 40m; and 100 x 50m,respectively. Tree plants with DBH of more than 10 cm at each site were 50, 47 and 42 (or 101 species in total), while small tree plants of 2-10cm in DBH were 78, 11 and 98 (or 203 species in total), respectively. The most dominant species were Ficus subcordata, Aphorosa sphaeridophora and Castanopsios rhamnifolia at each site, respectively. Based on the similarity indices, those sites were clustered. Species diversity and structure of the forest at each site were also discussed in relation to the natural succession of forest.